2016
DOI: 10.1096/fj.201600787rr
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic activation of estrogen receptor α increases mitochondrial function, energy expenditure, and brown adipose tissue

Abstract: Most satiety-inducing obesity therapeutics, despite modest efficacy, have safety concerns that underscore the need for effective peripherally acting drugs. An attractive therapeutic approach for obesity is to optimize/maximize energy expenditure by increasing energy-utilizing thermogenic brown adipose tissue. We used in vivo and in vitro models to determine the role of estrogen receptor β (ER-β) and its ligands on adipose biology. RNA sequencing and metabolomics were used to determine the mechanism of action o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 85 publications
2
63
1
Order By: Relevance
“…In a recent series of preclinical studies, [151][152][153] it was demonstrated that ERβ-specific ligands have powerful antiobesity effects and increase energy expenditure and mitochondrial activity in adipose tissues, including in the setting of ovarian hormone deficiency. In a recent series of preclinical studies, [151][152][153] it was demonstrated that ERβ-specific ligands have powerful antiobesity effects and increase energy expenditure and mitochondrial activity in adipose tissues, including in the setting of ovarian hormone deficiency.…”
Section: Estrogen Receptor Betamentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent series of preclinical studies, [151][152][153] it was demonstrated that ERβ-specific ligands have powerful antiobesity effects and increase energy expenditure and mitochondrial activity in adipose tissues, including in the setting of ovarian hormone deficiency. In a recent series of preclinical studies, [151][152][153] it was demonstrated that ERβ-specific ligands have powerful antiobesity effects and increase energy expenditure and mitochondrial activity in adipose tissues, including in the setting of ovarian hormone deficiency.…”
Section: Estrogen Receptor Betamentioning
confidence: 99%
“…While the mechanisms by which signaling through ERβ may have antiobesity effects are not clear, new evidence implicates ERβ as a primary mediator of 17β-E2's protective metabolic effects regarding adipose tissue mitochondrial activity. In a recent series of preclinical studies, [151][152][153] it was demonstrated that ERβ-specific ligands have powerful antiobesity effects and increase energy expenditure and mitochondrial activity in adipose tissues, including in the setting of ovarian hormone deficiency. 150 A major caveat is that the majority of these studies investigating isotype-specific effects of ER signaling have been done in rodent models, not humans.…”
Section: Estrogen Receptor Betamentioning
confidence: 99%
“…Body weight and body composition data from the experiments described in the manuscript were presented in our previous publication. 20 CON diet-fed mice consumed 173AE 12 g/ seven animals/week, while the HFD-fed vehicle-treated and b-LGND2-treated mice consumed 105 AE 17 g/seven mice/week and 111 AE 8 g/seven mice/week, respectively. At the end of 10 weeks, the animals were sacrificed and blood and tissues were collected for gene expression, histology, and metabolomics.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies from our group showed that one of the ER-b-selective agonists belonging to the isoquinolinone scaffold, b-LGND2, prevented high fat diet (HFD) induced body weight and adipose tissue gain, without affecting food consumption by acting peripherally by converting white adipose tissue (WAT) to brown adipose tissue (BAT). 19,20 This conversion of WAT to BAT by b-LGND2 resulted in an increase in thermogenesis and oxygen consumption, all culminating in weight loss. b-LGND2 was more effective than some of the commercial drugs used as comparator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation